If it's not what You are looking for type in the equation solver your own equation and let us solve it.
32=-9(3b+4)
We move all terms to the left:
32-(-9(3b+4))=0
We calculate terms in parentheses: -(-9(3b+4)), so:We get rid of parentheses
-9(3b+4)
We multiply parentheses
-27b-36
Back to the equation:
-(-27b-36)
27b+36+32=0
We add all the numbers together, and all the variables
27b+68=0
We move all terms containing b to the left, all other terms to the right
27b=-68
b=-68/27
b=-2+14/27
| 10(y-88)-46=4 | | 3x+17=51 | | 20-12g=-12g-20+2g | | 3(x−1)=2(x+3) | | -(b-56)=-4 | | 2x+30=x-23 | | -3(y-95)=66 | | 2(r-18)=-8 | | 1+12/3*7=x | | -4(5+2h)=22 | | g-3/7=3/2 | | 10=3(m+1)+1 | | h+2=10+5h | | 15=3-n | | -b-10=10-5-4b | | 5(d-73)-23=37 | | 9=2(n+3)+1 | | 0=-2(k+1) | | q-10=8+4q | | 2(h+1)+6=16 | | 10h/2=3 | | 17-u=14 | | 760=x²+18x | | 3(t+16)=18 | | 760=x^2+18x | | 6t=5t+4 | | 1/n=-1 | | H=t+4 | | 3(j-9)+1=19 | | 2(d-11)-4=4 | | k(7k+2)=5 | | 14x+64=6x-64 |